2024
DOI: 10.1038/s41598-024-53261-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel theta-controlled vibrotactile brain–computer interface to treat chronic pain: a pilot study

Phillip Demarest,
Nabi Rustamov,
James Swift
et al.

Abstract: Limitations in chronic pain therapies necessitate novel interventions that are effective, accessible, and safe. Brain–computer interfaces (BCIs) provide a promising modality for targeting neuropathology underlying chronic pain by converting recorded neural activity into perceivable outputs. Recent evidence suggests that increased frontal theta power (4–7 Hz) reflects pain relief from chronic and acute pain. Further studies have suggested that vibrotactile stimulation decreases pain intensity in experimental an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…The types оf neurofeedback used іn the studies considered include electroencephalographic (EEG) neurofeedback, infra-low frequency (ILF) neurofeedback, volitional limbic neuromodulation, SMR-based neurofeedback, alpha-wave neurofeedback, and rt-fMRI neurofeedback ( Jensen et al, 2013 ; Guan et al, 2015 ; Hassan et al, 2015 ; Goldway et al, 2019 ; Terrasa et al, 2020 ; Arina et al, 2022 ; Demarest et al, 2024 ). These studies have shown promising results, with notable reductions іn non-pain-related symptoms and pain relief іn patients with chronic pain ( Terrasa et al, 2020 ; Barbosa-Torres and Delgado, 2021 ; Shimizu et al, 2022 ) and with a significant impact оn pain intensity іn the immediate period ( Hesam-Shariati et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…The types оf neurofeedback used іn the studies considered include electroencephalographic (EEG) neurofeedback, infra-low frequency (ILF) neurofeedback, volitional limbic neuromodulation, SMR-based neurofeedback, alpha-wave neurofeedback, and rt-fMRI neurofeedback ( Jensen et al, 2013 ; Guan et al, 2015 ; Hassan et al, 2015 ; Goldway et al, 2019 ; Terrasa et al, 2020 ; Arina et al, 2022 ; Demarest et al, 2024 ). These studies have shown promising results, with notable reductions іn non-pain-related symptoms and pain relief іn patients with chronic pain ( Terrasa et al, 2020 ; Barbosa-Torres and Delgado, 2021 ; Shimizu et al, 2022 ) and with a significant impact оn pain intensity іn the immediate period ( Hesam-Shariati et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%